The coactivator dTAF(II)110/hTAF(II)135 is sufficient to recruit a polymerase complex and activate basal transcription mediated by CREB - Felinski, Edward A. (The National Academy of Sciences, 2001)
A specific TATA binding protein-associated factor (TAF), dTAF(II)110/hTAF(II)135, interacts with cAMP response element binding protein (CREB) through its constitutive activation domain (CAD), which recruits a polymerase complex and activates transcription. The simplest explanation is that the TAF is a coactivator, but several studies have questioned this role of TAFs. Using a reverse two-hybrid analysis in yeast, we previously mapped the interaction between dTAF(II)110 (amino acid 1–308) and CREB to conserved hydrophobic amino acid residues in the CAD. That mapping was possible only because CREB fails to activate transcription in yeast, where all TAFs are conserved, except for the TAF recognizing CREB. To test whether CREB fails to activate transcription in yeast because it lacks a coactivator, we fused dTAF(II)110 (amino acid 1–308) to the TATA binding protein domain of the yeast scaffolding TAF, yTAF(II)130. Transformation of yeast with this hybrid TAF conferred activation by the CAD, indicating that interaction with yTFIID is sufficient to recruit a polymerase complex and activate transcription. The hybrid TAF did not mediate activation by VP16 or vitamin D receptor, each of which interacts with TFIIB, but not with dTAF(II)110 (amino acid 1–308). Enhancement of transcription activation by dTAF(II)110 in mammalian cells required interaction with both the CAD and TFIID and was inhibited by mutation of core hydrophobic residues in the CAD. These data demonstrate that dTAF(II)110/hTAF(II)135 acts as a coactivator to recruit TFIID and polymerase and that this mechanism of activation is conserved in eukaryotes.